The effects of FinTechs on bank market power and risk taking behaviour in Kenya - David Ndwiga (Kenya Bankers Association (KBA), 2020)
The study seeks to investigate the nexus between market power and stability of the banking industry in pre FinTech period (2003 - 2009) and post FinTech entrance period (2010 - 2017). Specifically, the study seeks to investigate the effect of FinTech entrance on market power and later analyze the effect of market power changes on banking industry's risk appetite. Market power was measured by Lerner index while risk appetite was measured by net interest margin and credit risk. The estimation results from PVAR model finds that bank risk-taking behaviour is positively - related to increase in the market power following the FinTechs' entry.
Keywords: 330; Finanztechnologie; Bank; Marktmacht; Bankenliquidität; Kreditrisiko; Risikopräferenz; Kenia